Great Recession, Financialization and Marxian PoliticalEconomy - Bakır, Hasan; Bahtiyar, Görkem (My University, 2017)
Mainstream economic approaches, such as Keynesian and Neoclassical, agree one another in that the crises of capitalism should be handled within the capitalism. While Keynesians defend preemptive state intervention to avoid crises, neoclassical economics believe that the market will solve all problems without the need to resort to state action. After the Great Depression in 1930, Keynesian economics gained popularity, while neoclassical economics took over in the 1970s. Today, Keynesian economics became popular again in the aftermath of 2008 financial crisis. According to them, there is no alternative to the market system. Marxian explanation of 2008 financial crisis presents an alternative to the both. In this light, the aim of this study is to discuss the Marxian take on the 2008 global crisis, focusing on the phenomenon of financialization in this context.

Keynesyen ve Neoklasik iktisat gibi ana akım yaklaşımlar, kapitalizmin krizinin yine kapitalizm içinde kalınarak çözülebileceği üzerinde anlaşmaktadırlar. Keynesyenler krizi önleme konusunda devlet müdahalesini savunurken, Neoklasik iktisat devlet müdahalesine gerek kalmadan piyasanın bütün problemleri çözeceğine inanmaktadır. Keynesyenler, 1930’larda yaşanan Büyük Buhran sonrasında popüler olmuş fakat 1970’li yıllarda Neoklasik iktisat onların yerini almıştır. Günümüzde, Keynesyen iktisadın popülaritesi tekrar yükselmiştir. Her iki yaklaşım da, piyasa sisteminin bir alternatifi olmadığını ifade eder. Yaşanan kriz sürecine alternatif bir açıklama ise, Marksist teoriden gelmiştir. Bu çalışmanın amacı, küresel kriz sürecine yönelik ortaya konan bu alternatif açıklamayı finansallaşma bağlamında tartışmaktır.
Büyük Durgunluk, Finansallaşma ve Marksist Politik İktisat
Keywords: Krizler; Büyük Buhran; İktisadi Düşünce Okulları; Ana Akım İktisat; Marksist Politik İktisat; Crises; Great Recession; Economic Schools of Thought; Mainstream Economics; Marxian Political Economy